Placebo urban interventions: Observing Smart City narratives in Santiago de Chile. (February 2021) - Jirón, Paola; Imilán, Walter A; Lange, Carlos; Mansilla, Pablo
The implementation of the Smart City (SC) model in Santiago, Chile has not heralded any significant interventions in terms of scale, urban impact, amount invested, technological innovation or architectural design. Instead, material interventions have been small and have had little more than a superficial impact upon the perceptions of citizens. The significance of observing 'Smart' interventions in Santiago involves analysing their implementation under a provincialising lens in order to observe the way local experience transforms monist ways of thinking about SCs. Based on ethnographic observation of an SC intervention (in Paseo Bandera, Santiago de Chile), four principles of intervention were identified: democratisation of the city, spatial appropriation by citizens, social and technological innovation and local and territorialised interventions. These principles help to identify the intervention as an urban placebo, which the article argues works through the fictions of effective interventions and urban image improvement that seek to participate in worlding practices whilst, in reality, very little is being improved or effectively addressed in the city. Paseo Bandera SC intervention presents a narrative of modern, sustainable and technologically advanced urban planning in the form of specific material interventions, when in fact it involves very little modernity, sustainability or technology, and is little more than a continuation and evolution of the neoliberal urban model that exists in Chile.